Komunikasi Sastra pada Puisi Selamat Tahun Baru Kawan Karya Mustofa Bisri - Andika Hendra Mustaqim (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2018)
The purpose of this study was to explore literary to provide an understanding of communication in the poem Selamat Tahun Baru Kawan by KH Mustofa Bisri (Gus Mus) with a focus on dismantling the language system and sociocultural system. The approach of this study is qualitative and uses the content analysis method. Data collection techniques use documentation techniques. The data analysis technique starts from compiling a summary of the abstraction in the form of a body, explanation, and structuring. The results of this study indicate that language system in the poem by Gus Mus raises meaning that can be drawn in terms of denotative and connotative. Then, the diction game was also played by Gus Mus. Selection of diction shows a certain representation. Furthermore, rhyme and rhythm games are also important aspects of Gus Mus's poetry. In the socio-cultural system, in Gus Mus's poem the focus is on matters of faith which become identities in many of his poems. He insinuated the way to believe that many Muslims, especially in Indonesia, ignored the essence and tended to show more image. In addition, the socio-cultural elements that emerge are sentiments that can be parameters of social stability, and goals that are the direction of community movement. Not to be left behind is decisive power and dominance in society, and tension also plays with paradoxical narrative